2020
DOI: 10.1111/apa.15202
|View full text |Cite
|
Sign up to set email alerts
|

Active antibiotic discontinuation in suspected but not confirmed early‐onset neonatal sepsis—A quality improvement initiative

Abstract: Aim: To study whether a simple targeted intervention could reduce unwarranted antibiotic treatment in near-term and term neonates with suspected, but not confirmed early-onset sepsis. Methods: A quality improvement initiative in three Norwegian neonatal intensive care units. The intervention included an inter-hospital clinical practice guideline for discontinuing antibiotics after 36-48 hours if sepsis was no longer suspected and blood cultures were negative in neonates ≥ 34+0 weeks of gestation. Two units use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
5
15
0
Order By: Relevance
“…However, Dretvik et al observed some unexpected collateral benefit from their quality improvement initiative 6 . There was an overall 37% reduction in antibiotic treatment days from 11.4 to 7.2 per 100 near‐term and term infants.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…However, Dretvik et al observed some unexpected collateral benefit from their quality improvement initiative 6 . There was an overall 37% reduction in antibiotic treatment days from 11.4 to 7.2 per 100 near‐term and term infants.…”
supporting
confidence: 90%
“…In addition, it is very difficult to further reduce the treatment length from 49 hours in non-confirmed sepsis. However, Dretvik et al observed some unexpected collateral benefit from their quality improvement initiative6 . There was an overall 37% reduction in antibiotic treatment days from 11.4 to 7.2 per 100 near-term and term infants.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Dretvik and colleagues compared the duration of antibiotic therapy in suspected EOS in three Norwegian NICUs before and after implementation of an evidence-based guideline which was developed in order to reduce unwarranted antibiotic treatment. They did not find a significant reduction in antibiotic therapy duration in neonates treated for suspected EOS but the overall antibiotic use was reduced without affecting safety [26].…”
Section: Discussionmentioning
confidence: 89%